Evaluation Method of Datagram Congestion Control Protocol Over 4G Networks (S/O 12730) - Awang Nor, Shahrudin; Hassan, Suhaidi; Omar, Mohd Hasbullah; Katuk, Norliza; Che Mohamed Arif, Ahmad Suki (UUM, 2021)
This research is aimed for the performance evaluation of the implementation of Datagram Congestion Control Protocol (DCCP) over the 4G network, specifically LTE-Advanced. DCCP can be considered as a new transport protocol, which is delay-sensitive and error-insensitive, and like User Datagram Protocol (UDP), it is suitable as a transport protocol for multimedia data such as audio and video. But unlike UDP, DCCP is equipped with congestion control mechanism to control the congestion in the network. With this feature, it can ensure that network will not be overwhelmed with overloaded uncontrolled multimedia data that may cause, to a certain extent, the network to collapse. LTE-Advanced network is foreseen as a potential and future wireless network and will be fully implemented worldwide in very near future. LTE-Advanced can offer high speed data transmission capability broadband network compared to the existing 3G network. Mobile devices, such as smartphones, tablets, laptops, netbooks, etc are seen as a future of the Internet, with multimedia data, whether streaming or recorded, is becoming very popular. Hence, it is a motivation to study the performance of the multimedia data transport protocol over such network before the full implementation where the service to be delivered to the mobile users. Research methodology used in this research is via simulation using the network simulator NS-3. The main objective to be achieved is to get the real performance evaluation of DCCP as transport protocol over 4G network. As an expected result, the performance evaluation of DCCP over 4G network can be useful as a basis for the full implementation of 4G network carrying multimedia data, specifically audio and video data.